“To Study the Impact of Online Fraud and Scams on Online Purchasing Behaviour of Consumers in Ahmedabad City” - Gautam Dodiya; Dudhat, Dhruvi; Vidani, Jignesh (International Journal of Applied Economics, Accounting and Management (IJAEAM), 2024)
This research investigates the impact of online fraud and scams on the purchasing behaviour of consumers in Ahmedabad City, focusing on the prevalence of different types of scams, their repercussions, and strategies to reduce such risks. The study employs a mixed-methods approach, utilizing questionnaires and interviews to understand consumer perceptions. The research reveals a significant association between age and online shopping behaviour, highlighting variations in vulnerability, awareness, and response to fraud concerns across different age groups. The findings emphasize the crucial role of trust, security policies, and information-seeking behaviour in shaping consumer attitudes. With the global online fraud market projected to reach $5.7 trillion by 2025, this research provides valuable insights for e-commerce platforms and policymakers to tailor strategies, enhance security measures, and implement targeted interventions, fostering a safer online shopping environment